Faktor penentu kejayaan usahawan kuih tradisional di Daerah Papar, Sabah (Determinant Factors for the Success of Traditional Cookies Entrepreneurs in Papar District, Sabah) - Johan Johnes; Nur Faraeein Zainal Abidin; Jabil Mapjabil; Nur Izzah Nabilah Haron; Siti Hairah Taba; Corina Claire Alexander (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2018)
Local entrepreneurship is the catalyst for community development in some region. The Papar District is synonymous with one of the local entrepreneurship in Sabah which is the production of traditional cookies. The popularity of traditional cookies have brought the businesses into the international market and it has encouraged researchers to look at the factors that determine the success of traditional cookies entrepreneurs in Papar, Sabah. The main objective of this study is to examine the internal factors and external factors that have influenced the success in traditional cookies entrepreneurship. This study uses qualitative methods of informal interviews, in-depth interviews, participating involvement and observations. In this regard, 11 informants were involved in this study. Based on SWOT analysis results, this study has successfully determined the internal factors and external factors that contributes to the success of traditional cookies entrepreneurs in the Papar district. For the strength (S) aspect, the factors involved are the level of knowledge, business attitude, recipes, and business financial capital and communication skills. For weaknesses (W), factors such as weak in basic entrepreneurship, business capital constraints, negative attitudes in business, lack of communication skills and weak in management are the factors that affect the success of local entrepreneurs. Opportunities (O) analysis shows the aspects of financial assistance, the use of social media, entrepreneurship programs, customer demand and target markets have influenced the success factors of traditional cookies entrepreneurs in Papar, Sabah. Analysis of the threats (T) found that the aspects in product competition, large company domination, product quality, and production cost and resource shortage were identified as the threats factors. The results of this study are relevant especially to the stakeholders as it can be used as a strategic plan guide to develop a competitive small medium entreprenuer nationally and globally.